The authors acknowledged the Office of Department of Health in Nabire, Polytechnic of Health of the Ministry of Health of Jayapura, Papua, all nursing colleagues for supporting the study and our gratitude to all parties willing to participate in the study - Sukatemin Sukatemin; Ester Ester (Institute of Computer Science (IOCS), 2022)
The major role of nursing in the management of tuberculosis cases with comorbidities in remote areas is seldom exposed in a structured framework. This study aims to framework for tuberculosis patients with comorbidities in the Directly Observed Treatment Shortcourse (DOTS) program in the nursing profession. The research method was a Cross-Sectional Study with a descriptive design. Data collection was carried out during 2020 in all health service facilities at the public health center (Puskesmas) implementing the DOTS program in Nabire, Papua. The sample was 948 tuberculosis patients. The inclusion criteria were TB patients on anti-tuberculosis drug (OAT) treatment. The exclusion criteria were not TB patients or TB patients without OAT treatment. The results of this study indicated that with the nursing framework there were five stages, namely database creation, identification of priority problems, preparation of referrals, intervention, and evaluation. Bacteriologically confirmed samples were 73.7%, diagnosed with pulmonary tuberculosis at 68.7%, extrapulmonary tuberculosis at 1.3%, with comorbid HIV at 10%, and diabetes mellitus at 3%. After six months of treatment showed patients recovered from TB was 12.1%, died at 3.7% and 1.6% failed. In conclusion, the nursing framework helps in a structured and systematic way in handling TB cases in remote areas.